Mobile Web-Based Information System As Information For Searching For Boarding Houses For Students - Marlia Sari; Lusia Septia ER; Muhammad Junaidi (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2024)
Boarding houses or often called boarding houses are a necessity for the community, especially students and pupils, who are looking for a temporary place to live for those who are completing their education. Information about boarding houses usually comes from word of mouth and people don't yet know complete information about the boarding house. To overcome the problems that occur, this mobile web-based boarding house information system is useful for helping students and pupils in finding boarding house information that suits their wishes and making it easier for owners to market boarding houses. The method used to build a boarding house information system is to use the SDLC (System Development Life Cycle) method with the MySQL programming language as a database on XAMPP. This system is also supported by Google Maps which makes it easier for searchers to find the location of the desired boarding house. The final result of designing and building a mobile web-based boarding house information system can make it easier for students and students to find boarding houses.